Diverged Early From CtpB and CtpC, CtpA Has Evolved to Process D1 Precursor in Oxygenic Photosynthetic Organisms - Chang, Weidong; Li, Chenggang; Cui, Zheng; Li, Wei; Song, Haifeng; Chang, Han; Fu, Weihan; Wang, Chunyu; Huang, Ting; Luo, Yixin; Shan, Yelin; Wang, Yuhua; et al. (Frontiers in Plant Science, 2021)
C-terminal peptidase (Ctp) cleaves the C-terminal extension of the D1 precursor (pD1) to form mature D1. Among the three homologs CtpA, CtpB and CtpC in photosynthetic organisms only the first is capable of processing pD1 while the roles of CtpB and CtpC remain elusive. Phylogenetic analysis of Ctps from photosynthetic organisms revealed that CtpA has diverged early from CtpB and CtpC during evolution implying distinct roles for the Ctps. Analysis of Arabidopsis Ctp-deficient mutants revealed that pD1 processing was not affecetd in atctpb, atctpc, or atctpb/atctpc mutants, demonstrating that AtCtpA, not AtCtpB or AtCtpC, is responsible for cleaving the pD1 C-terminal extension. Ectopic expression of CtpAs from Synechococcus elongatus, Chlamydomonas reinhardtii, and Physcomitrella patens in atctpa rescued the lethal phenotype of the mutant indicating that SeCtpA, CrCtpA, and PpCtpA could process pD1 in Arabidopsis. Enzyme activity assays showed that PpCtpA and CrCtpA could convert pD1 into mature D1 in vitro. In contrast, expressing CtpB or CtpC from Arabidopsis, C. reinhardtii, or P. patens in atctpa did not rescue its D1 maturation deficiency, and enzyme activity assays also showed that neither CtpB nor CtpC could process pD1 in vitro. Taken together, we conclude that the function of pD1 processing by CtpA is conserved in photosynthetic organisms. It is possible that among other factors CtpA developed this function to initiate the formation of the oxygenic D1/D2 type PSII complex during evolution whereas CtpB or CtpC have other roles that are still unclear.